Geochemical modeling of CO2 emissions from volcanic soil microseepage: implications for greenhouse gas budget - Xianzhe Duan; Haoran Sun; Nan Li; Jiale Dou (Carbon Balance and Management)
Abstract As the global greenhouse effect intensifies, the emission and balance of greenhouse gases, particularly carbon dioxide (CO2), have become crucial for achieving global carbon neutrality. Volcanic geothermal regions, as major natural sources of carbon emissions, release substantial volume of greenhouse gases into the atmosphere in various ways including volcanic eruptions, soil microseepages, vents, and hot springs. Among these, soil microseepages are particularly important due to their widespread and persistent nature. However, the geochemical dynamics of CO2 release from soil microseepage in volcanic regions remain poorly understood. In this study, we propose a novel CO2 release model employing computational fluid dynamics (CFD) to model CO2 emissions from soil microseepage in volcanic regions. Our results provide important insights as follows: (1) Low porosity in subsurface strata inhibits CO2 penetration, while well-developed underground cracks and channels enhance release rates. (2) Favorable gas pathways enable CO2 to penetrate dense layers, and migrate upward, with migration patterns influenced by gas source pressure, temperature, and soil permeability. Slowing vertical migration increases horizontal diffusion and expands the effective surface release area. (3) Surface release is also influenced by external factors like wind speed, though these do not significantly affect underground seepage. (4) To improve the accuracy of CO2 flux measurements using the closed chamber method, it is recommended to reverse the initial slope of the CO2 concentration-time curve. This study provides critical data to enhance global carbon budget assessments and support efforts towards carbon neutrality.